Techno-Economic and Environmental Analysis of a Grid-Tied Solar PV System for an Institution of Higher Learning Using PVSyst: Case of the University of Botswana - Ditiro Setlhaolo,; Nokuthula Bitsang,; Anita Machola,; Sylvia Owczwareck, (International Journal of Scientific Research in Science and Technology, 2024)
The focus of this study is to design and simulate a grid tied solar PV system for a higher institution of learning using University of Botswana, Faculty of Engineering and Technology building as a case. The grid-connected system aimed at reducing the energy bill and contributes to the reduction of the CO2 emissions. The system uses the physical data and PVsyst software and OpenSolar and google earth to determine the key parameters crucial for the design of the project. Technical performance analysis of the proposed rooftop PV plant showed that the energy injected into the grid, with consideration of all losses amounts to 480MWh/year with a substantial lifetime carbon reduction of 991.2tons. The economic evaluation of the designed system showed that the project is profitable at the discontinued payback period of 8.63 years and the annual energy bill reduction of 32% is achieved. These results are beneficial to institutions and any other entity that would like to migrate from their use of conventional power in that they will gain an insight on their CO2 emission reduction and contribution to the national quota, their expected energy and cost savings. Governments and utilities can also benefit from these results in integrating with their energy and CO2 emissions.
Keywords: PV System; Grid-tied; CO2 Emissions; Economic Analysis; PVSyst; OpenSolar